Analysis of clinical characteristics of hemorrhagic fever with renal syndrome with acute pancreatitis: a retrospective study - Lihua Huang; Min Xiao; Xiaoling Huang; Jun Wu; Jiao Luo; Fuxing Li; Wei Gu (Annals of Medicine)
Objective This research aimed to analyze the impact of hemorrhagic fever with renal syndrome (HFRS) with acute pancreatitis (AP) on the severity and prognosis of patients, screen the risk factors of HFRS with AP, and establish a nomogram model.Methods Data were collected from HFRS patients at the First Affiliated Hospital of Dali University and Dali Prefecture People’s Hospital (2013-2023). Patients were divided into HFRS with AP (n = 34) and HFRS without AP groups (n = 356). Propensity Score Matching (PSM) and logistic regression analyzed the impact of AP on HFRS severity and short-term prognosis. LASSO-Logistic regression was used to screen risk factors and develop a nomogram model.Results After PSM, HFRS patients with AP had higher rates of Continuous Renal Replacement Therapy (CRRT) and/or mechanical ventilation use, , ICU admission, and 30-day mortalitycompared with those without AP (p < 0.05). Further analysis revealed that smoking (OR: 3.702), ferritin (OR: 1.002), white blood cell (OR), fibrinogen (OR: 0.463), and platelet (OR: 0.987) were risk factors for HFRS with AP (p < 0.05). A nomogram model was constructed based on these factors, to predict the risk of HFRS with AP, with an Area Under the Curve (AUC) of 0.90 (95% CI: 0.84–0.95). Additionally, the model calibration curve fit well according to the Hosmer-Lemeshow test (χ2=8.51, p = 0.39).Conclusion Patients with HFRS with AP exhibit higher disease severity and poorer prognosis. Smoking, elevated ferritin and white blood cell levels, decreased fibrinogen and platelet levels are more susceptible to developing AP.